HUBUNGAN KECAKAPAN KEPRAMUKAAN DENGAN KEDISIPLINAN SISWA SD IT INSAN UTAMA 2 PEKANBARU - Vira Hermaya; M. Jaya Adi Putra; Zufriady Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine is a correlation between scouting skills and students discipline of SD IT Insan Utama 2 Pekanbaru. Type of the research was quantitative research with a correlational approach. Populations used in this study were 81 scout students. Samples were selected by using saturated sampling techniques. Instruments used in this study were scouting skills questionnaires and student discipline questionnaires. Data were analyzed by using statistical analysis techniques. Based on the results of the data, it can be seen that the scouting skills were in a fairly good category with a percentage of 66.67% and the students discipline were in a fairly good category with 66.67%. Based on the results of the hypothesis testing, it was found that the correlation between scouting skills and students discipline was 0.398 of correlation value. Based on the results of significant calculations obtained t-count value 3.853 > t-table 1.990, then Ho was rejected and Ha was accepted. It means that there is a significant correlation between scouting skills and students discipline of SD IT Insan Utama 2 Pekanbaru. Then, based on the test results of the determinant coefficient, it was found that there is an influence of the contribution between variables at 15.8%. This means that there is a contribution of scouting skills of 15.8% to student discipline, while 84.2% is influenced by other factors not examined in this study.Key Words: Scouting Skills, Students Discipline